2011
DOI: 10.1124/mol.110.070789
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Loop 2 of the Free Fatty Acid Receptor 2 Mediates Allosterism of a Phenylacetamide Ago-Allosteric Modulator

Abstract: Allosteric agonists are powerful tools for exploring the pharmacology of closely related G protein-coupled receptors that have nonselective endogenous ligands, such as the short chain fatty acids at free fatty acid receptors 2 and 3 (FFA2/GPR43 and FFA3/GPR41, respectively). We explored the molecular mechanisms mediating the activity of 4-chloro-␣-(1-methylethyl)-N-2-thiazolylbenzeneacetamide (4-CMTB), a recently described phenylacetamide allosteric agonist and allosteric modulator of endogenous ligand functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
117
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(123 citation statements)
references
References 41 publications
(66 reference statements)
6
117
0
Order By: Relevance
“…Despite this, some subsequent studies have indicated very limited ability of this ligand to produce elevation of Ca 21 levels in transfected cells (discussed later). Moreover, further analyses of the pharmacological properties of this ligand revealed an ability to exert positive cooperativity with both C3 and C2, indicating that 4-CMTB behaves as an allosteric agonist at FFA2 (Lee et al, 2008;Wang et al, 2010;Smith et al, 2011). Mutagenic studies have revealed that extracellular loop 2 plays an important role in the allosteric effect of 4-CMTB.…”
Section: Ffa2/ffa3 Receptor Structure and Signal Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, some subsequent studies have indicated very limited ability of this ligand to produce elevation of Ca 21 levels in transfected cells (discussed later). Moreover, further analyses of the pharmacological properties of this ligand revealed an ability to exert positive cooperativity with both C3 and C2, indicating that 4-CMTB behaves as an allosteric agonist at FFA2 (Lee et al, 2008;Wang et al, 2010;Smith et al, 2011). Mutagenic studies have revealed that extracellular loop 2 plays an important role in the allosteric effect of 4-CMTB.…”
Section: Ffa2/ffa3 Receptor Structure and Signal Transductionmentioning
confidence: 99%
“…The main endogenous SCFAs (C2, C3, and C4) activate FFA2 and FFA3 with varying potency (denoted by the thickness of the arrow), and the rank order of activity is not maintained between human and mouse species orthologs (Hudson et al, 2012b). Synthetic allosteric agonists at FFA2 are represented by phenylacetamides, where 4-CMTB is the most potent ligand (Lee et al, 2008;Wang et al, 2010;Smith et al, 2011) and it maintains its activity across human and mouse FFA2 (Hudson et al, 2012b). Allosteric modulators at FFA3 are represented by a class of synthetic ligands that comprise allosteric agonists, such as AR420626, and allosteric antagonists, such as 2-methyl-5-oxo-4-(3-phenoxyphenyl)-N-(o-tolyl)-1, 4,5,6,7,8-hexahydroquinoline-3-carboxamide (compound 6) .…”
Section: Ffa2/ffa3 Receptor Structure and Signal Transductionmentioning
confidence: 99%
“…Somewhat surprisingly, although significant species variation has been observed among the orthosteric SCFAs at FFA2, 14 appears to show little variation in potency and activity between human, rodent [83] and bovine (unpublished observation) orthologues of FFA2. There is, however, also some indication that 14 may produce different signaling responses at FFA2 than the SCFAs, specifically 14 appears to be a full agonist in some pathways but only a partial agonist in others [89], perhaps suggesting some degree of functional selectivity. This, however, needs to be more clearly defined in future studies.…”
Section: Allosteric Ligands For Ffa2 and Ffa3mentioning
confidence: 98%
“…In particular, (S)-4-chloro--(1-methylethyl)-N-2-thiazolylbenzeneacetamide (14) was identified in a high throughput screen and found to be a selective ago-allosteric modulator of FFA2 [87]. As is often the case with allosteric ligands, subsequent attempts to explore the SAR of this series were unable to improve on its modest potency despite modification of all parts of the structure [88,89]. Defining the allosteric site where 14 binds has also presented a substantial challenge, with several modeling and mutagenesis studies unable to determine a precise mode of binding [88][89][90][91].…”
Section: Allosteric Ligands For Ffa2 and Ffa3mentioning
confidence: 99%
See 1 more Smart Citation